Analysis of Land Movement in Santur Village Using The Geographical Information System Method (SIG) - Nauli, Fitri; Hellyward, James (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
The village of Santur is located in a tropical climate area with a varied surface relief including flat, hilly, and undulating terrain. The natural landscape in this area presents a potential for moderate to high soil movement, which can lead to land movement. The objective of this research is to map the areas in Santur village that are prone to soil movement. The study utilizes Geographic Information System (GIS) methodology to produce a vulnerability map of soil movement in the research area. Based on the soil movement model developed by Puslittanak in 2004, at least 6 supporting maps are required to generate a soil movement map in the study area, namely regional geological maps, rainfall maps, geomorphological maps, soil type maps, and rock type maps. Therefore, the parameters used in this research include soil type, rock type, land slope, geological formation, land use, and rainfall. All these parameters undergo weighting using map overlay techniques. The research findings indicate that areas in Santur village predominantly exhibit landslide threats, with very high vulnerability on the northern side around mining areas, as well as several other high-risk points within the research area and moderate vulnerability mostly spread across Santur village. Consequently, the mapping results of landslide-prone areas in Santur village can serve as a reference for the government in urban and regional planning for the city of Sawahlunto. Desa Santur merupakan daerah beriklim tropis dan memiliki relief permukaan datar, berbukit, dan bergelombang. Bentangan alam yang ada di daerah ini mempunyai potensi gerakan tanah yang sedang hingga tinggi sehingga bisa menyebabkan terjadinya pergerakan tanah. Tujuan dari penelitian ini untuk memetakan daerah di desa Santur yang rawan terhadap pergerakan tanah. Penelitian ini menggunakan metode Sistem Informasi Geografis (SIG) untuk mendapatkan peta kerentanan pergerakan tanah di daerah penelitian. Berdasarkan model pergerakan tanah yang dikembangkan oleh Puslittanak pada Tahun 2004, dibutuhkan setidaknya 6 peta pendukung untuk menghasilkan peta pergerakan tanah di sekitar wilayah penelitian yaitu, peta geologi regional, peta curah hujan, peta geomorfologi, peta jenis tanah, dan peta jenis batuan. Sehingga, parameter yang digunakan dalam penelitian ini adalah jenis tanah, jenis batuan, kemiringan lahan, formasi geologi, tataguna lahan, dan curah hujan. Semua parameter ini dilakukan pembobotan menggunakan overlay peta. Berdasarkan hasil penelitian menunjukkan bahwa daerah di desa Santur dominan memiliki tingkat ancaman longsor dengan kerawanan sangat tinggi pada sisi utara di sekitar daerah penambangan, serta ada beberapa titik lokasi lainnya, kerawanan tinggi dibeberapa lokasi daerah penelitian, dan kerawanan sedang mayoritas yang tersebar di daerah Desa Santur. Dengan demikian, peta hasil pemetaan daerah rawan pergerakan tanah di desa Santur ini dapat menjadi acuan bagi pemerintah untuk pembuatan rencana tata ruang dan wilayah Kota Sawahlunto.